Anti-TNF modulation reduces myocardial inflammation and improves cardiovascular function in systemic rheumatic diseases. (1st November 2018) - Ntusi, Ntobeko A.B.; Francis, Jane M.; Sever, Emily; Liu, Alexander; Piechnik, Stefan K.; Ferreira, Vanessa M.; Matthews, Paul M.; Robson, Matthew D.; Wordsworth, Paul B.; Neubauer, Stefan; Karamitsos, Theodoros D.
Abstract: Background: Rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA) are common disorders associated with increased rates of cardiovascular disease (CVD), but the contribution of cytokine-induced inflammation to impaired cardiovascular function in these conditions remains poorly understood. Objectives: We assessed the effect of anti-TNF therapy on myocardial and vascular function, myocardial tissue characteristics and perfusion in inflammatory arthropathy and systemic rheumatic disease (IASRD) patients, using cardiovascular magnetic resonance (CMR). Methods: 20 RA patients, 7 AS patients, 5 PsA patients without previously known CVD scheduled to commence anti-TNF therapy and 8 RA patients on standard disease modifying antirheumatic drugs underwent CMR at 1.5 T, including cine, tagging, pulse wave velocity (PWV), T2-weighted, native and postcontrast T1 mapping, ECV quantification, rest and stress perfusion and late gadolinium enhancement (LGE) imaging. Results: Following anti-TNF therapy, there was significant reversal of baseline subclinical cardiovascular dysfunction, as evidenced by improvement in peak systolic circumferential strain (p < 0.001), peak diastolic circumferential strain rate (p < 0.001), and total aortic PWV, (p < 0.001). This was accompanied by a reduction in myocardial inflammation, as assessed by T2-weighted imaging (p = 0.005), native T1 mapping (p = 0.009) and ECV quantification (p = 0.001), as well as in serum inflammatory markers like CRP (p < 0.001) and ESR (p < 0.001), and clinical measures of disease activity (DAS28-CRP, p = 0.001; BASDAI, p < 0.001). A trend towards improvement in myocardial perfusion was observed (p = 0.07). Focal myocardial fibrosis, as detected by LGE CMR was not altered by anti-TNF therapy (p = 0.92). Conclusions: Anti-TNF therapy reduces subclinical myocardial inflammation and improves cardiovascular function in RA, AS and PsA. CMR may be used to track disease progression and response to therapy. Future CMR-based studies to demonstrate effect of anti-TNF therapy modulation of vascular structure and function on hard clinical events and outcomes would be useful. Highlights: We hypothesized that anti-TNF therapy would result in an improvement in myocardial and vascular characteristics in patients with IASRDs. We show that CMR can detect subclinical cardiovascular involvement and track response to anti-TNF therapy in asymptomatic RA, AS and PsA patients. Anti-TNF therapy improves strain, diastolic strain rate, aortic stiffness, and myocardial edema (T2-weighted, T1 and ECV quantification). While a trend towards improvement in myocardial perfusion was observed, this did not reach statistical significance. These novel observations were supported by parallel improvements in inflammatory parameters (CRP and ESR) and in disease activity indices.